Occurrence of Additional Canals in Mandibular Lower Anteriors In Between Male and Female Patients - KUMAR. S, DHINESH; S, DEEPAK.; RAMANATHAN, VISALAKSHI (The journal of contemporary issues in business and government, 2021)
The endodontic treatment with excellent outcomes depends on the critical identification of the root and its canals anatomy. The successful identification of these anatomies guaranteed the pulp tissue extirpation completely, with efficiency in chemo-mechanical cleaning and shaping. All these lead to the most proper three-dimensionally root canal obturation with the most reliable inert filling. The purpose of this study is to provide clinical data on the presence of additional canals in mandibular anterior teeth among males and females.Patients reported from June 2019 to March 2020 were reviewed. 82000 patient records were reviewed and data related to patients undergone Root canal therapy in mandibular lower anteriors. Data includes age, gender and number of additional canals in lower anteriors. The collected data was tabulated in the excel sheet. Statistical analysis was done using SPSS software (version 9.0.3). The prevalence of patients with additional canals in mandibular anteriors was 8.1% . For females, the prevalence of additional canals was 3.24% whereas in males it is 4.86%. However, there is no relation between the gender and presence of additional canals in mandibular anteriors.